TRANSFORMING TO A DEMOCRATIC ISLAMIC UNIVERSITY: AN APPLICATION OF FUTURISTIC APPROACHES - Sulaiman, Ahmad; Supriyanto, Supriyanto (J-MPI (Jurnal Manajemen Pendidikan Islam), 2019)
Change is a double-edged knife. It is both beneficial and harmful. A changing organization must first recognize the needs for change before planning a radical transformation. However, some organizations can fail to identify and devise effective measures to transform since the transforming layers are beyond overt variables: such as the aspects of ideology and metaphors. This paper is dealing with the need for change in a private university in Indonesia. Unsuccessful effort to manage the change has produced unproductive conflicts in the university. To generate an effective transformation plan, the researchers employed, ethnography, an embedded participant observation, to gather rich data. Followed by a combination of two futuristic methods namely Causal Layered Analysis (CLA) and backcasting to deeply comprehend the fabrics of the present, generate an alternative and preferred future, and present ideal measures to actualize the preferred future along with potential risks. The result suggests the university to transform all covert and overt layers in concert to be a progressive democratic Islamic university.